Analisis Kinerja Guru Di Sekolah SMP Katolik Kota Manado Dengan Evaluasi CIPP - Antonius Heatubun; Fransiskus Talaud (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
This study aims to evaluate teacher performance Catholic junior high schools in Manado using the CIPP (Context, Input, Process, Product) Evaluation model. The aspects assessed include the context of the work environment, qualifications, resources, teaching processes, and student learning outcomes. This research method is qualitative with an evaluative descriptive approach, involving principals and teachers as informants. Data collection techniques included observation, documentation and in-depth interviews. The results show that environmental conditions, educational qualifications, work experience, professional training and adequate facilities greatly affect teacher performance. Teachers play an important role in education with the responsibility of planning, implementing and evaluating learning. Teacher performance must be optimal to ensure quality education. Effective classroom management and positive interactions between teachers and students were also found to play an important role in improving student learning outcomes. The conclusion shows that improving teacher performance in Catholic junior high schools in Manado can be achieved by improving the work environment, providing continuous training and adequate facilities.